Managing higher education diversity in a climate of public sector reform - Meek, V. Lynn (Evaluations and investigations programme higher education divison, 1998)
This book introduce about issues and perspectives in the Australian context. System profile and institutional studies. Conclusion: diversity and Australian higher education.